PROFESIONALITAS DOSEN PERGURUAN TINGGI KEAGAMAAN ISLAM SWASTA (PTKIS) DI OGAN KOMERING ULU TIMUR SUMATERA SELATAN - Dedi Setiawan (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
This study aims to explore and describe the professionalism of lecturers through the implementation of the three duties of higher education including: education and teaching, research and community service at the Private Islamic Religious University (PTKIS) Ogan Komering Ulu Timur, South Sumatra. This type of research is a qualitative study, with a phenomenological approach. Data is taken from two PTKIS namely STIT Misbahul Ulum Gumawang and STKIP Nurul Huda Sukaraja. The findings of the research show that: 1) aspects of education and teaching, the ability of respondents in designing, implementing, and evaluating the lecture process is quite good; 2) aspects of research and scientific publications are not so optimal, product research results are still very limited. Meanwhile, scientific publications are published twice a year through local journals that are already ISSN; 3) aspects of community service carried out in a form that is independent and group. The factors supporting and inhibiting the professionalism of lecturers: 1) supporting factors include: academic qualifications, academic atmosphere, budget, teaching and learning facilities; 2) inhibiting factors: academic qualifications, inadequate memberships, not so conducive academic atmosphere, teaching and learning facilities are not yet complete. Furthermore, efforts to develop the professionalism of lecturers through: participation in training activities, involvement in activities outside the campus, support from university leaders, and competency development through improving education levels. In addition, the process of fostering professionalism of lecturers is also carried out by Kopertais Region VII Sumbagsel as an umbrella for PTKIS.